The John Adair Handbook of Management and Leadership - Edited by Thomas, Neil (New Delhi Viva Books (Pvt.) Ltd., 2015)
This text is rich in practical advice and guidance and addresses key areas such as setting and achieving goals and objectives, decision making and problem solving, creative and innovative thinking, self-development, and much more.
Include Tables.
Keywords: Management -- Leadership